Liberal arts for the Christian life - Davis, Jeffry C.; Ryken, Philip Graham, 1966-; Ryken, Leland (Wheaton, IL : Crossway, 2012)
For over forty years, Leland Ryken has championed and modeled a Christian liberal arts education. His scholarship and commitment to integrating faith with learning in the classroom have influenced thousands of students who have sat under his winsome teaching. Published in honor of Professor Ryken and presented on the occasion of his retirement from Wheaton College, this compilation carries on his legacy of applying a Christian liberal arts education to all areas of life. Five sections explore the background of a Christian liberal arts education, its theological basis, habits and virtues, differing approaches, and ultimate aims. Contributors including Philip Ryken, Jeffry Davis, Duane Litfin, John Walford, Alan Jacobs, and Jim Wilhoit analyze liberal arts as they relate to the disciplines, the Christian faith, and the world. Also included are a transcript of a well-known 1984 chapel talk delivered by Leland Ryken on the student's calling and practical chapters on how to read, write, and speak well. Comprehensive in scope, this substantial volume will be a helpful guide to anyone involved in higher education, as well as to students, pastors, and leaders looking for resources on the importance of faith in learning. - Publisher.
"This book has been written by some of professor Ryken's many colleagues from Wheaton College as a way of honoring his service as a teacher, scholar, mentor, and friend." pg.12
Includes bibliographical references and index.
Keywords: Education, Higher -- Religious aspects -- Christianity; Education, Humanistic -- Philosophy; Learning and scholarship -- Religious aspects -- Christianity; Church and college